The Implementation of Administrative Services through Application of Digital Technology in Medokan Ayu to Increase the Service Quality for People - Simbolon, Delima; Laksono, Bintang; Casmiwati, Dewi (Pencerah, 2024)
Public service is one of the efforts made by the government to provide services to the community. In Surabaya, one of the most important public services is the population administration service, which is managed by the city's Population and Civil Registration Office. To access this service, Surabaya residents have the option to take care of their population administration at the local urban village office or RW hall. Thus, the Surabaya City Government seeks to bring services closer to the community and improve the ease of access to administrative services. This research aims to describe and analyze how the implementation of bureaucratic reform on service performance in Medokan Ayu urban village. The research method used in this research is descriptive qualitative. Data collected by observation, interview and documentation methods. This research uses the theoretical reference put forward by Agus Dwijayanto (2006) in Ismoyo (2017), which identifies five main indicators to measure the performance of the public bureaucracy. These indicators include: (1) Productivity, (2) Service Quality, (3) Responsiveness, (4) Responsiveness (5) Accountability. The results show that population administration services in Kelurahan Medokan Ayu face significant challenges, especially related to the limitations of competent human resources and the lack of socialization of administrative programs. However, with reforms through the application of digital technology, such as barcode systems and e-Kios, service productivity has increased substantially despite the limited number of employees. The quality of service has also been improved by providing additional services such as outreach for underprivileged residents and making it easier for them to access the services they need.